Pengaruh Digital Marketing, E-WOM, Destination Branding dan Green Marketing Terhadap Visit Intention Desa Wisata - Nandika, Thania Sanique; Sadat, Andi Muhammad; Febrilia, Ika (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2023)
ABSTRACT This study aims to determine the effect of Digital Marketing on Visit Intention, the effect of e-WOM on Visit Intention, the effect of Destination Branding on Visit Intention, and the effect of Green Marketing on Visit Intention to the Tourist Village, of Bogor. The data collection method used is a survey method with an instrument in the form of a questionnaire. The research sample collected amounted to 238 respondents. The software used in data analysis is SPSS Version 25.0. and SEM (Structural Equation Model) from LISREL. Based on the research results, it can be concluded that the first hypothesis